Extragonadal germ cell tumor of the posterior mediastinum in a child complicated with spinal cord compression: a case report - Dong Keon Yon; Tae Keun Ahn; Dong Eun Shin; Gwang Il Kim; Moon Kyu Kim (BMC, 2018)
Abstract Background Germ cell tumors (GCTs) in children are rare neoplasms with diverse pathological findings according to the site and age of presentation. The most common symptoms in children with mediastinal GCTs, which are nonspecific, are dyspnea, chest pain, cough, hemoptysis, vena cava occlusion syndrome, and fatigue/weakness. Because of these nonspecific symptoms, it is difficult to suspect a mediastinal mass. A posterior mediastinal tumor causing spinal cord compression is an important example of an oncologic emergency arising from a neurogenic tumor. Case presentation Children with posterior mediastinum GCTs can be easily mistaken as having a neurogenic tumor because of site of tumor origin. We treated our 7-year-old patient with emergency decompression surgery and high-dose steroid pulse therapy to prevent secondary injury to the spinal cord. Primary injury was a result of spinal cord compression due to the initial manifestation of GCT in the posterior mediastinum. Cisplatin-based chemotherapy was also administered. The patient was followed up regularly for 3 years and is undergoing rehabilitation without any signs of recurrence. Conclusions We present an extremely rare case of a child with paraparesis caused by extradural spinal cord compression as the initial manifestation of GCT in the posterior mediastinum. The child was treated with emergency decompression surgery and high-dose pulse steroid therapy to prevent secondary injury to the spinal cord.